2022
DOI: 10.4103/jcd.jcd_549_21
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of shear bond strength of a bioactive material to composite resin using three different universal bonding agents: An in vitro study

Abstract: Background: Calcium silicate-based cements or bioceramics have revolutionized and simplified pulp-capping procedures due to its versatility and accessibility. Aim: This study aimed to assess the shear bond strength (SBS) of a bioceramic material to composite resin at two aging periods and with three universal adhesives. Materials and Methods: Forty-eight samples of Biodentine with a height of 2 mm and internal diameter of 4 mm were prepared. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In the literature, studies examine the bond strength between Biodentine and its superstructure for periods ranging from 24 h to one month and immediately after mixing ( Nekoofar et al, 2018 ). When the µSBS of the filling material applied on Biodentine was measured in 12 min and 24 h, it was observed that the strength increased ( Kudva et al, 2022 ; Nekoofar et al, 2018 ) or did not change ( Odabaş, Bani & Tirali, 2013 ) in different studies. In our study, we tried to prevent time from being an influential factor in SBS by keeping the incubation time constant.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, studies examine the bond strength between Biodentine and its superstructure for periods ranging from 24 h to one month and immediately after mixing ( Nekoofar et al, 2018 ). When the µSBS of the filling material applied on Biodentine was measured in 12 min and 24 h, it was observed that the strength increased ( Kudva et al, 2022 ; Nekoofar et al, 2018 ) or did not change ( Odabaş, Bani & Tirali, 2013 ) in different studies. In our study, we tried to prevent time from being an influential factor in SBS by keeping the incubation time constant.…”
Section: Discussionmentioning
confidence: 99%